Weed management in sunflower: A review on challenges and opportunities: WEED MANAGEMENT IN SUNFLOWER: A REVIEW ON CHALLENGES AND OPPORTUNITIES - A SOLAIMALAI; M JAYAKUMAR; V SANJIV KUMAR; S MANOHARAN; K BASKAR; G RAVINDRA CHARY (Journal of Oilseeds Research, 2022)
Weed management is a science-based decision-making process that coordinates the use of macro and micro-environment information, weed biology and ecology, and all available technologies to control weeds by the most economical and ecologically viable methods. The concept of weed management is not new and many advances have been made in recent years in India. Weeds compete with crop plants for nutrients, soil water, space and sunlight causing poor growth and yield losses. The extent of yield losses caused by weeds depends up weed density and type of weed flora. The age old practice of controlling weeds in sunflower by hand weeding and hoeing is time consuming, more expensive and tedious although it is more effective. However, timely weed management may not be possible manually due to non-availability of labourers and high rate of wages during peak farm operation. Under such condition, use of herbicides is the need of the hour for crop production. Therefore, use of newly introduced pre-emergence and post emergence herbicides along with cultural and mechanical methods is needed for effective weed management and increase the productivity of sunflower.